Solar desalination with charcoal briquettes from plants as an additional absorption sorbent - Jafri, Muhamad; Tarigan, Ben; Adoe, Dominggus (Heritage and Sustainable Development, 2024)
Water is the most abundant substance on Earth, but only 2.5% can be used for drinking and farming; the rest is seawater containing much salt. Solar desalination is a great tool to solve this problem for small families and remote areas. However, the disadvantage of using solar power is still the low productivity of distillate because it depends on the season, region, and intensity of solar radiation. Solar radiation heat absorbing and storing materials are a favorable solution in increasing evaporation rate, efficiency, and total distillate. Many have been developed to date, but these materials require more expenditure to be used as radiation heat sinks and stores. Charcoal derived from wood has high thermal energy absorption and porosity. Four desalination devices were used, namely using an additional absorber made from Kapok wood (Ceiba pentandra) coded CP_60, Gamal wood (Gliricidia sepium) coded GS_60, Kusambi wood (Schleichera oleosa) coded SO_60, and without additional absorber as a comparison. All desalination devices have the same shape and size, simple, with an area of 0.09 m2 each. Before the additional absorber base material is used, drying, charring, grinding, meshing, pressing, and briquetting are carried out. The test results show that the additional absorber of natural materials affects the evaporation rate, desalination efficiency, and total distillate water. The distillation device using Gamal wood (Gliricidia sepium) additional absorber material, coded GS_60, provides maximum performance such as distillate water yield every 30 minutes and total distillate 124 ml/0.09 m2, 28.19% efficiency, and evaporation rate.